2019
DOI: 10.4236/jss.2019.75005
|View full text |Cite
|
Sign up to set email alerts
|

Research on Employee Pressure and Resistance Caused by Organizational Change—A Case Study of Jingyi Network Co., Ltd.

Abstract: According to the theory of organizational change, this paper takes Jing Yi Network Technology Co., Ltd. as an example to analyze the problem of employee pressure and employee resistance caused by organizational change. In order to more comprehensively discuss the causes of employee pressure and resistance under organizational change, the impact of employee pressure and resistance on enterprise development, and the countermeasures to reduce the pressure and resistance of employees, it is carried out from four a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The final reason for employee resistance appears as a result of the conflict of interest between the employee and the goals of organizational change. (Zhang, 2019). Some of the employees even oppose the change because of their personality and their values.…”
Section: Resistance To Organizational Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…The final reason for employee resistance appears as a result of the conflict of interest between the employee and the goals of organizational change. (Zhang, 2019). Some of the employees even oppose the change because of their personality and their values.…”
Section: Resistance To Organizational Changesmentioning
confidence: 99%
“…In other words, it can be evaluated as a kind of evolution towards improving the state of the organization, institution, etc. Organizational change is a dynamic process that allows for long-term development by adapting to changes in the internal and external environment (Zhang, 2019). Organizational change is defined as an activity that aims to move from the current state to a desired future state in order to increase effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce resistance, training is required, which explains why adapting to change can be difficult for employees. In a study, Zhang (2019) posited that pressure and employee resistance are caused by organizational change. Using Jingyi Network Co. Limited as a case study for understanding the nature of employees' resistance to change, Zhang (2019) identified changes in organizational structure, personnel, technology, and culture as categories when dealing with change management.…”
Section: Resistance To Organizational Changementioning
confidence: 99%
“…In a study, Zhang (2019) posited that pressure and employee resistance are caused by organizational change. Using Jingyi Network Co. Limited as a case study for understanding the nature of employees' resistance to change, Zhang (2019) identified changes in organizational structure, personnel, technology, and culture as categories when dealing with change management. Zhang (2019) concluded that members would resist the introduction of new technologies or any structural change because they are afraid of uncertainty, failure, and collective interests that are uncoordinated in the change processes.…”
Section: Resistance To Organizational Changementioning
confidence: 99%